Postural and Fatigue Analyses for Ergonomic Workstations Design as an Integrated Approach to Sustainable Workplaces - Realyvásquez-Vargas, Arturo; Maldonado-Macías, Aide Aracely; García-Alcaraz, Jorge Luis (Springer, 2021)
Deficient workstation designs are an important risk factor of suffering musculoskeletal disorders (MSDs) among operators in manufacturing companies. Postural and fatigue analyses can provide valuable information for the ergonomic design of workstations, as well as increasing the sustainability of manufacturing companies. The objective of this research is to propose a novel integrated approach by using postural and fatigue analyses for the ergonomic design and improvement of workstations as a strategy to increase sustainability of manufacturing companies. The proposed methodology comprises three stages: (1) workstations prioritization, (2) postural assessment and fatigue analyses using Rapid Upper Limb Assessment (RULA) and Muscle Fatigue Analysis (MFA), as well as (3) intervention and control stage. To validate this integrated approach, a case study was conducted analyzing the manual tasks from a group of employees in two production lines in a manufacturing company. As main results, 16 workstations were analyzed using the proposed methodology. In three of them the risk level for MSDs was found as moderate and reduced after ergonomic interventions. Absenteeism decreased by 88% and the production rate was increased in 31.35% after four weeks of the ergonomic design implementation. As a result, the integration of postural and fatigue analyses may lead to the ergonomic design for workstations and their improvement. Consequently, this approach can facilitate the increase of sustainability in manufacturing companies and employees’ well-being by making a better use of the human resources, reducing absenteeism, and increasing production rates and performance.